Sintesa Precipitated Calcium Carbonate (PCC) Dari Cangkang Kerang Darah ( Anadara Granosa) Dengan Variasi Jenis Asam Dan Waktu Karbonasi - Zikri, Ahmed; Amri, Amun; Zultiniar, Zultiniar; Yelmida, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Precipitated Calcium Carbonate (PCC) can be synthesized from blood cockle shell through three methods, namely the method of solvay, soda caustic, and carbonation. The method used in this research that was the carbonation process in the modification, the use of acid solvent during the slaking process to obtain higher yields. The purpose of this research was to synthesize precipitated calcium carbonate (PCC) of blood cockle shell by varying the type of solvent and acid carbonation time. A number of blood cockle shell powder was calcined at 900oC temperature to calcium oxide (CaO) form, then CaO was dissolved into some acid solvents (HNO3, HCl, and CH3COOH). Furthermore, the carbonation process with carbonation time variation 30, 60, and 90 minutes. Based on AAS analysis CaO content in the blood cockle shells was 76.66%, which detected as aragonite crystals. The highest yield of PCC was 84.42% for 90 minute carbonation time by using of HNO3 as solvent. For the XRD patterns it recognized that PCC contained mixture vaterit and calcite crystals. It also was supported by SEM analysis.Keywords: Blood cockle shell, Carbonation, Precipitated Calcium Carbonate (PCC), Variations acid.